Chronic lymphocytic leukaemia: the role of T cells in a B cell disease. (3rd April 2019) - Man, Stephen; Henley, Peter
Summary: Chronic lymphocytic leukaemia (CLL) has long been thought to be an immunosuppressive disease and abnormalities in T‐cell subset distribution and function have been observed in many studies. However, the role of T cells (if any) in disease progression remains unclear and has not been directly studied. This has changed with the advent of new therapies, such as chimeric antigen receptor‐T cells, which actively use retargeted patient‐derived T cells as "living drugs" for CLL. However complete responses are relatively low ( 26%) and recent studies have suggested the differentiation status of patient T cells before therapy may influence efficacy. Non‐chemotherapeutic drugs, such as idelalisib and ibrutinib, also have an impact on T cell populations in CLL patients. This review will highlight what is known about T cells in CLL during disease progression and after treatment, and discuss the prospects of using T cells as predictive biomarkers for immune status and response to therapy.